Evaluation of the psychometric properties of the Arabic version of the Depression, Anxiety, and Stress Scale- 21 items (DASS-21) – A descriptive study on a sample of adolescents in Jeddah- Saudi Arabia - Al-Shetaiwi, Walaa Salem; Al-Dhobaiban, Nawal Abdullah (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to assess psychometric characteristics and conduct confirmatory factor analysis on a sample of male and female adolescents in Jeddah, Saudi Arabia. In line with the descriptive approach, this study was conducted on 416 participants (60.6% of males, 39.9% of females), using a depression, anxiety and stress scale consisting of 21 items, distributed on three dimensions (depression, anxiety, stress), and confirmatory factor analysis was performed. (CFA) to examine the factorial structure of the scale. The results of all matching indicators resulted in an acceptable agreement for the model, and the results showed that the scale had good reliability in internal consistency (alpha, omega coefficient), in addition to achieving approximate and differential validity. As the Arabic version of DASS-21 showed good psychometric properties, the current research contributes to confirming it as a reliable and valid tool for assessing depression, anxiety and stress among Saudi adolescents. The study recommends conducting additional studies to confirm the characteristics of the Arabic version of the scale in other population groups of Saudis, in addition to working to increase public awareness about depression, anxiety and stress among adolescents and their parents.